2016
DOI: 10.1111/bjd.14425
|View full text |Cite
|
Sign up to set email alerts
|

Segmental basal cell naevus syndrome caused by an activating mutation in smoothened

Abstract: Aberrant sonic hedgehog signalling, mostly due to PTCH1 mutations, has been shown to play a central role in the pathogenesis of basal cell carcinoma (BCC), as well as in basal cell naevus syndrome (BCNS). Mutations in smoothened (SMO) encoding a receptor for sonic hedgehog have been reported in sporadic BCCs but not in BCNS. We report a case with multiple BCCs, pits and comedones in a segmental distribution over the upper part of the body, along with other findings compatible with BCNS. Histopathologically, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 15 publications
4
31
0
1
Order By: Relevance
“…46 The mutation is likely to be associated with a spectrum of negative and positive selective consequences during organismal growth and homeostasis, depending on cell type, which most likely explains the apparent evolution of skin lesions and low mutation levels in blood (negative selection) and the predisposition to tumorigenesis (positive selection). The association between segmental BCNS and SMO p.Leu412Phe in a recent report 45 is compatible with a later occurrence of the somatic mutation during development than in subjects with the classical CJS phenotype.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…46 The mutation is likely to be associated with a spectrum of negative and positive selective consequences during organismal growth and homeostasis, depending on cell type, which most likely explains the apparent evolution of skin lesions and low mutation levels in blood (negative selection) and the predisposition to tumorigenesis (positive selection). The association between segmental BCNS and SMO p.Leu412Phe in a recent report 45 is compatible with a later occurrence of the somatic mutation during development than in subjects with the classical CJS phenotype.…”
supporting
confidence: 57%
“…For example, vismodegib is a clinically approved SMO inhibitor that contacts the extracellular domain and ligand-binding pocket. Interestingly, in a recent report of a subject with segmental BCNS associated with the identical SMO p.Leu412Phe substitution, 45 treatment with vismodegib for 4 months led to cessation of the appearance of new lesions and shrinkage of some existing BCCs. However, other reports have suggested that the p.Leu412Phe substitution confers resistance to vismodegib, supporting a role for Leu412 in autoinhibition and/or structural stability.…”
mentioning
confidence: 99%
“…CJS has unusual abdominal symptomatology associated with smooth muscle hamartomas on the mesentery and surface of the bowel; motility disorders and upper gastrointestinal bleeding are frequent [34]. The identical SMO mutation has also been identified in several tumors, particularly involving the skin or brain; these are potentially treatable using hedgehog pathway inhibitors [35]. CDC45 encodes a key component of the machinery of DNA replication, present in all eukaryotes, so the identification of mutations in craniosynostosis may appear surprising.…”
Section: Recently Identified Disease Genesmentioning
confidence: 99%
“…We believe that our case belongs to the spectrum of Gorlin syndrome (MIM #109400) because most of the biopsies in our patient demonstrated classical nodular, pigmented, adenoid and superficial basal cell carcinomas (BCCs) (Fig. 2a–c in our article) . This is not congruent with the findings typical of Happle–Tinschert syndrome (HTS), in which the skin lesions are basaloid follicular hamartomas (BFHs) by definition.…”
mentioning
confidence: 53%